2006
DOI: 10.1159/000093961
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Gelatinase-Associated Lipocalin and Renal Function after Percutaneous Coronary Interventions

Abstract: Background/Aims: The value of neutrophil-gelatinase-associated lipocalin (NGAL), a novel biomarker in the detection of acute renal failure in children after cardiac surgery, has been highlighted in previous studies. The incidence of percutaneous coronary intervention (PCI) increases, which may possibly result in increased incidences of contrast nephropathy, its potentially serious complication. Therefore, the aim of our study was to assess prospectively NGAL in patients undergoing elective PCI in relation to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
155
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 28 publications
8
155
2
3
Order By: Relevance
“…These results, together with our previous (9) and current data and the published evidence on an association between pediatric lupus nephritis and lipocalin-2 up-regulation (20), strongly support our assertion that urinary lipocalin-2 is a promising potential marker of renal involvement in SLE. As mentioned above, previous studies have indicated that other forms of renal injury, including ischemia, nephrotoxic drugs, or infection, can also up-regulate lipocalin-2 expression in the kidneys (14)(15)(16)(17)(18)(19). Therefore, elevations in urinary lipocalin-2 are not specific to nephritis in SLE.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results, together with our previous (9) and current data and the published evidence on an association between pediatric lupus nephritis and lipocalin-2 up-regulation (20), strongly support our assertion that urinary lipocalin-2 is a promising potential marker of renal involvement in SLE. As mentioned above, previous studies have indicated that other forms of renal injury, including ischemia, nephrotoxic drugs, or infection, can also up-regulate lipocalin-2 expression in the kidneys (14)(15)(16)(17)(18)(19). Therefore, elevations in urinary lipocalin-2 are not specific to nephritis in SLE.…”
Section: Discussionmentioning
confidence: 94%
“…Urinary lipocalin-2 appeared very early in the postoperative period (within 2 hours) and preceded any elevation in the serum creatinine level by 1-3 days. Recently, several additional studies have demonstrated that urinary lipocalin-2 could serve as an early biomarker of acute renal injury secondary to a variety of other conditions, such as adverse effects due to transplantation or percutaneous coronary intervention, renal failure due to infection, and cisplatin nephrotoxicity (16)(17)(18)(19). Moreover, in a recently published cross-sectional study of patients with childhoodonset SLE, Brunner et al reported that urinary lipocalin-2 correlated with renal disease activity (20).…”
mentioning
confidence: 99%
“…Contrast media induces renal cell apoptosis in a dose-dependent manner (Romano et al 2008). These changes can occur within a few hours and may lead to kidney injury (Galtung et al 2000;Bachorzewska-Gajewska et al 2006;Romano et al 2008). Increased plasma osmolar gap at hour 6 may reflect kidney damage related to contrast media.…”
Section: Discussionmentioning
confidence: 99%
“…CIAKI can prolong hospital stay and lead to early and late worse outcomes (McCullough 2008). Some studies have been performed to determine predictors or biomarkers for the early detection of CIAKI, including serum cystatin C (Briguori et al 2010) and neutrophil gelatinase-associated lipocalin (Bachorzewska-Gajewska et al 2006;Hirsch et al 2007). However, measurements of these parameters may not be available in practice.…”
mentioning
confidence: 99%
“…Furthermore, NGAL concentration in both urine and plasma rises rapidly in a dose-dependent manner that is proportional to the degree of acute kidney damage 7 and is detectable at a point where injury is still potentially limitable and reversible. 8 Therefore, NGAL may enable prospective diagnostic and prognostic stratification in the primary care setting.…”
Section: Advantages Over Existing Technologymentioning
confidence: 99%